Impact of C-Reactive Protein Levels on Differentiating of Severe Fever With Thrombocytopenia Syndrome From Japanese Spotted Fever. (7th October 2020) - Kawaguchi, Takeshi; Umekita, Kunihiko; Yamanaka, Atsushi; Hara, Seiichiro; Yamaguchi, Tetsuro; Inoue, Eisuke; Okayama, Akihiko
Abstract: Background: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging viral hemorrhagic fever in China, Korea, and Japan. Japanese spotted fever (JSF), which belongs to spotted fever group rickettsioses, is also endemic to Western Japan. Patients with SFTS and those with JSF display many of the same clinical manifestations. Sudden fever, rash, tick bite, and neurological and gastrointestinal symptoms may be seen in both infections, but the frequency and severity of each disease have not been compared and studied. Because laboratory confirmation of pathogens takes time, it is important to predict diagnosis of SFTS vs JSF based on the features of the clinical characteristics at the initial presentation, particularly in primary care settings. Methods: We conducted a case series review at 4 medical facilities in Miyazaki, Japan. Based on the medical records, clinical and laboratory characteristics were compared between patients with SFTS and those with JSF. Results: Eighty-one patients were enrolled in this study, including 41 with SFTS and 40 with JSF. The absence of rash ( P < .001), leukopenia ( P < .001), and normal C-reactive protein (CRP) levels ( P < .001) were the variables distinguishing SFTS from JSF. Normal CRP levels (≤1.0 mg/dL) had a 95% sensitivity (84%–99%) and 97% specificity (87%–100%) for SFTS, with a positive likelihood ratio of 37.1 (5.35–257). Conclusions: Normal serum CRP levels were shown to differentiate SFTS from JSF with a very high probability.